Hypervalent Iodine Reagents as Powerful Electrophiles - Brown, Michael; Farid, Umar; Wirth, Thomas (Synlett, 2013)
Hypervalent iodine reagents have been investigated as very powerful electrophiles in many different reactions. Efficient formation of new carbon–heteroatom bonds as well as carbon–carbon bonds can be achieved typically under mild reaction conditions with these metal-free reagents. Enantiomerically pure reagents provide the potential for stereoselective reactions and this aspect is highlighted in this account.1 Introduction2 Stereoselective Reactions3 Reactions with Alkenes3.1 Iodolactonizations3.2 Oxyaminations of Alkenes3.3 Aziridinations of Alkenes4 α-Functionalization of Carbonyl Compounds and Catalysis5 Rearrangements6 Arylations7 Oxidations8 Summary and Outlook
Keywords: alkenes; catalysis; electrophiles; hypervalent iodine; stereoselective synthesis